2014
DOI: 10.4319/lo.2014.59.3.0840
|View full text |Cite
|
Sign up to set email alerts
|

Lakes as sensors in the landscape: Optical metrics as scalable sentinel responses to climate change

Abstract: As the lowest point in the surrounding landscape, lakes act as sensors in the landscape to provide insights into the response of both terrestrial and aquatic ecosystems to climate change. Here a novel suite of climate forcing optical indices (CFOI) from lakes across North America is found to respond to changes in air temperature, precipitation, and solar radiation at timescales ranging from a single storm event to seasonal changes to longerterm interdecadal trends with regression r 2 values ranging from 0.73 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 60 publications
3
83
1
1
Order By: Relevance
“…The optical properties of lakes provide particularly useful metrics for measuring ecosystem change (Vincent et al, 1998) as they not only convey information on the quantity of particulate and dissolved material but also its quality (Williamson et al, 2014). Furthermore, understanding how the optical properties of particulate and dissolved material in lakes influence the underwater light field and water-leaving radiative signal is important for the development and application of remote sensing techniques for lake monitoring and assessment, but also for their application to lake carbon studies.…”
Section: Importance Of Cdom In Lakesmentioning
confidence: 99%
“…The optical properties of lakes provide particularly useful metrics for measuring ecosystem change (Vincent et al, 1998) as they not only convey information on the quantity of particulate and dissolved material but also its quality (Williamson et al, 2014). Furthermore, understanding how the optical properties of particulate and dissolved material in lakes influence the underwater light field and water-leaving radiative signal is important for the development and application of remote sensing techniques for lake monitoring and assessment, but also for their application to lake carbon studies.…”
Section: Importance Of Cdom In Lakesmentioning
confidence: 99%
“…The waters in autumn indicated a higher level of pollution. Previous studies have exhibited the COD, NH 3 -N, TN, and TP accounted for 44.14%, 53.14%, 82.15% and 78% of the total pollutants, respectively [37]. A large number of farmland with remains of pesticide and fertilizer, household refuse and livestock dung existed in the Yinma River watershed.…”
Section: Pollution Statusmentioning
confidence: 92%
“…Further, GLEON science has demonstrated that the choice of physical model can have a large and significant influence on estimates of gas exchange across lakes spanning a productivity gradient , in some cases resulting in a switch from a lake being considered net autotrophic versus heterotrophic. Regarding the important role of lakes and reservoirs in the global carbon cycle, variation in dissolved organic carbon among lakes can help explain their thermal responses to external energy inputs (Read and Rose 2013) and has important implications for how lakes respond as sentinels of climate change (Williamson et al 2014, O'Reilly et al 2015. While dozens of papers using more than one lake can be cited within the GLEON context, the aforementioned studies exemplify the collaborative nature of GLEON through data sharing (http://gleon.org/data).…”
Section: Comparative Studiesmentioning
confidence: 99%